Effect of Solvent Pre-Treatment on the Leaching of Copper During Printed Circuit Board Recycling - Ahmed Tarek Ismail Mohamed; Giuliana Schimperna; Gianluca Cantoni; Francesca Demichelis; Debora Fino; Sara Perucchini; Francesca Rubertelli; Francesco Laviano (Recycling)
Printed circuit boards (PCBs) are fundamental components of electronic devices, acting as an important source of various valuable metals such as copper, gold, and silver. Efficient recycling methods that offer high recovery rates are essential to the full reutilization of these materials. Hydrometallurgical leaching is a prominent technique for metal recovery, but its efficiency can be significantly enhanced through solvent pre-treatment. In this study, an experimental analysis of the material composition of different categories of PCBs is presented. In addition, the study evaluates the influence of particle size on the subsequent copper leaching process and the efficiency of copper recovery. These investigations aim to better understand the material composition of PCBs and propose an optimized material recovery technique. The study finds that there are significant variances among the different categories of PCBs investigated, allowing a more informed handling process of WEEE. This research suggests that solvent pretreatment using DMSO for PCB particle sizes between 5.6 mm and 2 mm would be a good optimization technique, mitigating the drawbacks of treating fine particles while maintaining appealing recovery efficiency.